Cholesterol metabolism regulator SREBP2 inhibits HBV replication via suppression of HBx nuclear translocation - Yang, Fan; Hu, Feng; Song, Hongxiao; Li, Tie; Xu, Fengchao; Xu, Jing; Wang, Le; Wang, Fei; Zhu, Yujia; Huang, Mian; Gao, Yanli; Rao, Min; et al. (Frontiers in Immunology, 2025)
The intricate link between cholesterol metabolism and host immune responses is well recognized, but the specific mechanisms by which cholesterol biosynthesis influences hepatitis B virus (HBV) replication remain unclear. In this study, we show that SREBP2, a key regulator of cholesterol metabolism, inhibits HBV replication by interacting directly with the HBx protein, thereby preventing its nuclear translocation. We also found that inhibiting the ER-to-Golgi transport of the SCAP-SREBP2 complex or blocking SREBP2 maturation significantly enhances HBV suppression. Notably, we demonstrate that the C-terminal domain (CTD) of SREBP2, rather than its N-terminal domain (NTD), mediates this inhibition by interacting with HBx and promoting its extracellular secretion, thus reducing nuclear HBx accumulation. These findings reveal a novel regulatory pathway that links cholesterol metabolism to HBV replication via SREBP2-mediated control of HBx localization. This insight provides a potential basis for new therapeutic strategies against HBV infection, addressing an important global health issue.